Study of Security Threats and Challenges in Internet of Things Systems - et. al., Rohit Chawla, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The interpretability and secured communication are major challenge in internet of things. The embedding of wireless device has low energy and bandwidth. The low energy and bandwidth cannot effort computational overhead and compromised with security threats. Primary the conventional cryptography algorithm is applied for generation and sharing of key for mode of communication. The conventional cryptography algorithms have several bottleneck issues related to generation of key and distribution of key. The NIST models provides the secured communication channel in the environments of mobility. Lack of integrity, confidentiality and authorization process of data transmitted over the network of internet of things used the concept of key generation and allocation. The process of key generation and authentication provides the authorization and authentication of data over the internet of things. In this paper present the review of security threats of internet of things.